Factors Influencing Green Fashion Purchase Decisions: The Role of Green Brand Image, Electronic Word of Mouth, and Customer Perception with Green Attitude Mediation - Fahlevi, Tengku Reza; Sofriana Imaningsih, Erna (Dinasti Publisher, 2025)
This study explores the influence of Green Brand Image, Electronic Word of Mouth (E-WOM), and Customer Perception on Purchase Decision, with Green Attitude acting as a mediating factor, within the context of local green fashion products. As sustainability becomes a critical concern in the fashion industry, understanding consumer behavior toward eco-friendly products is essential for developing effective marketing strategies. Using a sample of 190 consumers from the Jabodetabek region, this research employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze the data. The findings reveal that Green Brand Image and Customer Perception significantly enhance Green Attitude, while Electronic Word of Mouth showed no significant impact. Furthermore, Green Attitude is found to have a strong and positive influence on Purchase Decision, highlighting the pivotal role of pro-environmental attitudes in driving consumer choices. Interestingly, while Green Brand Image does not directly affect Purchase Decision, Customer Perception demonstrate significant and positive impacts, however, this is different from Electronic Word of Mouth, which has no significant effect on Purchase Decision. Additionally, Green Attitude partially mediates the relationship between Green Brand Image and Purchase Decision and partially mediates the effects of Customer Perception, however, Green Attitude does not mediate the relationship between Electronic Word of Mouth and Purchase Decision. These results underscore the importance of fostering a strong green brand identity, leveraging positive online reviews, and educating consumers about the benefits of sustainable fashion. The study provides valuable insights for marketers aiming to promote local green fashion products and align with the growing demand for environmentally responsible consumption.